BUILDING AFFORDABILITY: AN EXPLORATION OF INCREMENTAL HOUSING DESIGN - Ujianto, Bayu Teguh; Iqbal, Muhammad Nelza Mulki (Border: Jurnal Arsitektur, 2025)
In Indonesia, the availability and quality of housing is a significant challenge. One potential solution that needs to be explored is the incremental housing strategy, which can provide options for users as their needs and income grow. This research aims to explore and develop affordable housing design ideas that specifically target the criteria of subsidized housing in Indonesia, based on the exploration of the national regulation related to the subsidized housing, and developed from the principles of affordable housing design such as the separation of functions and mass, the exploration of structure and materials, and the use of a cohesive form. Using design-based research as the design method, the research resulted in two alternative ideas for affordable housing. The design development as well as construction cost estimates use standard commercial building materials to get an idea of the possibility of building affordable housing with standard materials. This research is a valuable step in the exploration of ideas for affordable housing in Indonesia and will provide a valuable reference for future research and development of affordable housing in Indonesia.